Nuclear PKM2: a signal receiver, a gene programmer, and a metabolic modulator - Tsan-Jan Chen; Chun-Hsien Wu; Mien-Chie Hung; Wen-Ching Wang; Hsing-Jien Kung (Journal of Biomedical Science)
Abstract Pyruvate kinase M2 (PKM2) is a key enzyme involved in glycolysis, yet its role in cancer extends far beyond metabolic flux. Unlike its isoform PKM1, PKM2 exhibits unique regulatory properties due to alternative splicing and dynamic structural plasticity, enabling it to translocate into the nucleus. Once nuclear, PKM2 functions as a signal receiver, gene programmer, and metabolic modulator by acting as a co-transcriptional activator and protein kinase. In this capacity, nPKM2 (nuclear PKM2) orchestrates the transcription of genes involved in glycolysis, lipogenesis, redox homeostasis, and cell cycle progression, thereby reinforcing the Warburg effect and promoting tumor growth, metastasis, and resistance to stress. In this regard, nPKM2 can be considered as the oncogenic component of PKM2. This review consolidates current knowledge on the structural basis of PKM2 assembly and the post-translational modifications that govern its oligomeric state and nuclear import. We also explore emerging therapeutic strategies aimed at targeting nPKM2, including small-molecule modulators that stabilize its cytosolic tetrameric form or disrupt its nuclear functions. Ultimately, the multifaceted roles of nuclear PKM2 underscore its significance as a critical oncoprotein and a promising target for precision cancer therapy.